Lower Income Levels in Australia Are Strongly Associated With Elevated Psychological Distress: Implications for Healthcare and Other Policy Areas - Isaacs, Anton N.; Enticott, Joanne; Meadows, Graham; Inder, Brett (Frontiers in Psychiatry, 2018)
Background: Australia is a high-income country with increasing income inequality. It is unclear whether Australia’s well-developed mental healthcare system is making a difference to population mental health and the Federal Government has targeted outcomes accountability in service funding strategies. In high-income countries, evidence generally suggests that income inequalities increase mental disorders among the poor. This study examined psychological-distress rates - a marker of mental ill- health – as varying by income among Australians living within and outside of capital cities. Methods: Secondary data analysis was undertaken using the population-level mental health indicator of the Kessler Psychological Distress Scale (K10) as reported for 12,332 adults in the 2011/2012 National Health Survey (NHS) of Australia. K10 scores of 22 and higher indicated high/very-high distress, and 30 and higher denoted very-high distress. Very-high distress levels are strongly predictive of serious mental illness. Results: Among the poorest one-fifth of Australians, 1 in 4 people have psychological distress at a high/very-high level; this compares to about 1 in 20 people in the richest one-fifth of Australians. About 1-in-10 people making up the poorest one-fifth of Australians have current very-high distress, and this reduces to less than 1-in-50 people in the richest one-fifth. These disparities are consistent both within and outside of capital cities. The national prevalence of elevated distress within income quintiles varies greatly, with Poor/Rich Quintile Ratios of typically 4-5 for high/very-high levels and 7-8 for very-high levels. These effects operate more powerfully in areas marked by higher scores on the Index of Relative Socioeconomic Disadvantage. Conclusions: Altering the strong association of lower income levels in Australia with elevated psychological distress would require a multi-dimensional social policy and healthcare approach. To assess the effectiveness of adopted strategies, population level indicators need to be developed with regular data-collection. The Poor/Rich quintile ratio (P/R QR) for high/very high K10 scores is a potential candidate for a mental health inequality outcome indicator since it is easily calculated from data obtained from a regularly conducted national survey, is easily understood and resonates with a wider audience. Further research on the development of such indicators is also needed.